2014
DOI: 10.1177/0907568213519137
|View full text |Cite
|
Sign up to set email alerts
|

The negotiation of culture in foster care placements for separated refugee and asylum seeking young people in Ireland and England

Abstract: Little is known about separated asylum seeking young people in foster care. This article addresses this gap by drawing together findings from qualitative research conducted with separated refugee and asylum seeking young people in two studies -one in England and one in Ireland. Focusing on the role of culture, the authors examine similar findings from the two studies on the significance of culture in young people's experiences of foster care. Culturally 'matched' placements are often assumed to provide continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 21 publications
4
30
0
1
Order By: Relevance
“…In their review of risk and protective factors as they pertain to the mental health of displaced and refugee children, Fazel et al (2012) found that being able to maintain one's sense of cultural identity, however self-defined, was important, though integrating into the new society also served as a protective factor. These findings reflect the findings of my own research in the Irish context (Ní Raghallaigh and Gilligan, 2010;Ní Raghallaigh, 2013;Ní Raghallaigh and Sirriyeh, 2015). For example, in Ní Raghallaigh and Gilligan (2010) we refer to two of the coping strategies used by unaccompanied refugee children.…”
Section: Integration and Acculturationsupporting
confidence: 84%
See 3 more Smart Citations
“…In their review of risk and protective factors as they pertain to the mental health of displaced and refugee children, Fazel et al (2012) found that being able to maintain one's sense of cultural identity, however self-defined, was important, though integrating into the new society also served as a protective factor. These findings reflect the findings of my own research in the Irish context (Ní Raghallaigh and Gilligan, 2010;Ní Raghallaigh, 2013;Ní Raghallaigh and Sirriyeh, 2015). For example, in Ní Raghallaigh and Gilligan (2010) we refer to two of the coping strategies used by unaccompanied refugee children.…”
Section: Integration and Acculturationsupporting
confidence: 84%
“…For many child refugees, very practical aspects of living might differ significantly between the country of asylum or resettlement and their country of origin. A range of different people, including parents, peers, professionals, and carers, can be helpful in navigating these differences (Ní Raghallaigh and Gilligan, 2010;Ní Raghallaigh, 2013;Ní Raghallaigh and Sirriyeh, 2015). In the following quotation, a friend helped a young person to get used to the public transport system: Raghallaigh, 2007, p. 172) For accompanied refugee children parents will of course usually serve as a source of support in terms of negotiating the new cultural environment.…”
Section: Adjusting To the New Culturementioning
confidence: 99%
See 2 more Smart Citations
“…UNHCR (1992, p. 92) guidance in this respect states that 'every effort must be made to place children in foster families or groups of similar ethnic, cultural, linguistic, and religious background'. Generally, according to Ní Raghallaigh and Sirriyeh (2015), young people in studies in England and Ireland considered it to be important to maintain continuity in relation to their cultures of origin. However, 'matching' with foster carers was not the only means for achieving this.…”
Section: Research By Stanleymentioning
confidence: 99%